2020
DOI: 10.3390/v12070785
|View full text |Cite
|
Sign up to set email alerts
|

Oropouche Virus Infects, Persists and Induces IFN Response in Human Peripheral Blood Mononuclear Cells as Identified by RNA PrimeFlow™ and qRT-PCR Assays

Abstract: Oropouche orthobunyavirus (OROV) is an emerging arbovirus with a high potential of dissemination in America. Little is known about the role of peripheral blood mononuclear cells (PBMC) response during OROV infection in humans. Thus, to evaluate human leukocytes susceptibility, permissiveness and immune response during OROV infection, we applied RNA hybridization, qRT-PCR and cell-based assays to quantify viral antigens, genome, antigenome and gene expression in different cells. First, we observed OROV replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Studies on the related Oropouche virus indicate that the virus enters the CNS in mice by at least 3 different routes: by the neural route, by crossing the blood-brain barrier, and by the Trojan horse mechanism using infected leukocytes and monocytes. 14,16 In the present study, the brain stem was the most severely affected area in the majority of animals showing meningoencephalitis. Viral RNA was most consistently and most abundantly found in the spinal cord, brain stem, and diencephalon.…”
Section: Discussionsupporting
confidence: 48%
“…Studies on the related Oropouche virus indicate that the virus enters the CNS in mice by at least 3 different routes: by the neural route, by crossing the blood-brain barrier, and by the Trojan horse mechanism using infected leukocytes and monocytes. 14,16 In the present study, the brain stem was the most severely affected area in the majority of animals showing meningoencephalitis. Viral RNA was most consistently and most abundantly found in the spinal cord, brain stem, and diencephalon.…”
Section: Discussionsupporting
confidence: 48%
“…We therefore determined the levels of cytokines in the conditioned medium of OROV-infected human brain slices by ELISA. Elevated levels of cytokines have been described as an important initial response to experimental virus infection, including against OROV ( Rempel et al, 2005 ; Kawanokuchi et al, 2006 ; Amorim et al, 2020 ). Interestingly, we observed a significant increase in TNF-α release by brain slices infected with OROV, as compared to control slices ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Once inside the rodent CNS, OROV infection results in glial activation and neuronal cell death ( Rodrigues et al, 2011 ; Santos et al, 2012 ). It has been shown that OROV infects human leukocytes and monocytes, which could result in CNS invasion by the Trojan horse mechanism ( de Souza Luna et al, 2017 ; Amorim et al, 2020 ). Despite these important findings of OROV neuroinfection, the human brain susceptibility to OROV infection has not yet been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Research is primarily focused on understanding the mechanism by which OROV infects the CNS. Experimental animals such as mice and hamsters have been used to study the infection ( Ribeiro Amorim et al., 2020 ; Almeida et al., 2021 ). In some studies, animals inoculated with OROV developed systemic infection with neurological motor impairment and paralysis, suggesting hematogenous transmission to the brain and liver ( da Silva Menegatto et al., 2023 ).…”
Section: Infection and Immunitymentioning
confidence: 99%